2015
DOI: 10.3109/08958378.2015.1110217
|View full text |Cite
|
Sign up to set email alerts
|

N-acetylcysteine attenuates cigaret smoke-induced pulmonary exacerbation in a mouse model of emphysema

Abstract: Exposure of mice with emphysema to CS exacerbated the pulmonary damage, and NAC reduced the CS-mediated pulmonary damage by preventing oxidative damage and reducing inflammatory responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Nevertheless, the effect of NAC intervention did show a trend for attenuation of adverse cellular responses after diesel emissions exposure. These findings are in accordance with previous research [134,208] [163]. Kumar (2016) has shown that NAC treatment can effectively reduce oxidative stress-induced inflammation in vitro [163].…”
Section: -3)supporting
confidence: 93%
See 2 more Smart Citations
“…Nevertheless, the effect of NAC intervention did show a trend for attenuation of adverse cellular responses after diesel emissions exposure. These findings are in accordance with previous research [134,208] [163]. Kumar (2016) has shown that NAC treatment can effectively reduce oxidative stress-induced inflammation in vitro [163].…”
Section: -3)supporting
confidence: 93%
“…This suggests that NAC intervention may not be an effective intervention against the adverse effects of diesel emission exposure in the COPD lung. In contrast to this, Wang (2015) found that NAC intervention can reduce inflammation, oxidative stress and overall pulmonary damage after exposure to cigarette smoke exposure [134]. Additionally, Rogliani (2016)…”
Section: -3)mentioning
confidence: 99%
See 1 more Smart Citation
“…In AP-induced lung inflammation, recent studies showed that NAC inhibits two critical mechanisms by which air pollutants induce an inflammatory response, the ROS-mediated activation of MAPK and nuclear factor kappa B (NF-kB) signaling pathways Ping et al, 2019). Regarding the regulation of pro-inflammatory cytokines, most studies assessed the BAL fluid and lung tissue and found that NAC decreased the levels of IL-1β, IL-6, and TNF-α (Wang et al, 2015;Zhang et al, 2018;Ping et al, 2019;Wang Review C. et al, 2020;Wang J. et al, 2020). NAC was also beneficial in downregulating ICAM-1 expression (Liu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Because of such promising results, NAC has been used as a positive antioxidant control in several experimental models to identify other antioxidant strategies to treat emphysema and other COPD complications. For example, in a hybrid murine model in which emphysema was induced by porcine pancreatic elastase (PPE) and exacerbated by CS particulate matter, NAC treatment reduced CS-mediated pulmonary damage by preventing oxidative stress and reducing inflammatory responses [ 188 ]. In addition, Nrf2-GSH signaling was shown to be important for the protective effects of NAC against CS-induced injury in ATII cells.…”
Section: Oxidative Stress and Inflammation In Copd And Emphysemamentioning
confidence: 99%